Market Size, Competition, and the Product Mix of Exporters - Mayer, Thierry; Melitz, Marc J.; Ottaviano, Gianmarco I. P. (American Economic Review, 2014)
We build a theoretical model of multi-product firms that highlights how competition across market destinations affects both a firm’s exported product range and product mix. We show how tougher competition in an export market induces a firm to skew its export sales toward its best performing products. We find very strong confirmation of this competitive effect for French exporters across export market destinations. Theoretically, this within-firm change in product mix driven by the trading environment has important repercussions on firm productivity. A calibrated fit to our theoretical model reveals that these productivity effects are potentially quite large. (JEL D21, D24, F13, F14, F41, L11)